2023
DOI: 10.1158/0008-5472.can-23-0296
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Hijacks the miRNA Regulatory Pathway in Cancer

Abstract: Extensive studies have focused on the misregulation of individual miRNAs in cancer. More recently, mutations in the miRNA biogenesis and processing machinery have been implicated in several malignancies. Such mutations can lead to global miRNA misregulation, which may promote many of the well-known hallmarks of cancer. Interestingly, recent evidence also suggests that oncogenic KRAS mutations act in part by modulating the activity of members of the miRNA regulatory pathway. Here, we highlight the vital role mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 145 publications
0
11
0
Order By: Relevance
“…Thus we are led to speculate that cells able to adapt to chronic Ras-mediated signalling may become cancerous, in part, by sometimes activating stemness pathways that also confer reoviral susceptibility. We are therefore intrigued by the recent observation that Ras expression can modulate miRNA signalling, opening new possibilities for altering multiple downstream pathways, including cellular stemness [ 95 ]. In addition, an investigation of primitive gut stem cells or induced stem cells in the digestive tract that are possible natural hosts for viral infection in humans and other animals could yield further insights into mechanisms of viral cytolysis [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus we are led to speculate that cells able to adapt to chronic Ras-mediated signalling may become cancerous, in part, by sometimes activating stemness pathways that also confer reoviral susceptibility. We are therefore intrigued by the recent observation that Ras expression can modulate miRNA signalling, opening new possibilities for altering multiple downstream pathways, including cellular stemness [ 95 ]. In addition, an investigation of primitive gut stem cells or induced stem cells in the digestive tract that are possible natural hosts for viral infection in humans and other animals could yield further insights into mechanisms of viral cytolysis [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in the literature [74], oncogenic mutations in factors involved in miRNA biosynthesis, processing, and export machinery are associated with many cancers. The majority of these oncogenic mutations in the microprocessing complex and export machinery result in a decrease in miRNA biosynthesis, leading to global dysregulation of miRNAs and the mRNA transcripts they regulate.…”
Section: Oncogenic Mutations In Key Factors Involved In the Mirna Bio...mentioning
confidence: 99%
“…For example, it has been shown that genetic deletion or amplification, epigenetic methylation of miRNA genomic loci, and alterations affecting the transcription factor-mediated regulation of primary miRNA (pri-miRNA) as well as components involved in the miRNA biogenesis pathway frequently alter miRNA expression and function in many cancers. In addition, recent data indicate that other factors including oncogenic drivers such as mutations in the KRAS gene can also affect global miRNA biogenesis and effector function, leading to global miRNA dysregulation [74]. Because of this, miRNAs and their dysregulation have gained attention both from academia and industry as a research discipline both for understanding disease biology [59,[75][76][77] and to develop them as potential diagnostic, prognostic, and predictive biomarkers as well as drug targets or as therapeutics [47,48,51,59,67,78].…”
Section: Introductionmentioning
confidence: 99%
“…These mutations can lead to global miRNA deregulation which may promote hallmarks of cancer. Interestingly, recent evidence proposes that oncogenic KRAS mutations modulate the activity of members of the miRNA regulatory pathway and consequently enhance tumorigenesis [ 79 ]. miRNAs are now being developed as diagnostic and as predictive or prognostic tools.…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%